*How to solve for y when the value of x is a negative number for the equation y=x2-x-6 *

*When I plug in -7 for x I get 49-(-7)-6. So is the equation 49+7-6 or do you add -7 and -6 to get -13 and then subtract that from 49? I'm not sure if the answer is 36 or 50? Trying to help my son!*

Your equation is: x^2 - x - 6

Substituting for x = -7, we get

(-7)^2 - (-7) - 6

OK now,

-(-7) is the same as (-1)*(-7)

And two negative numbers multiplied together is a positive number

So, -(-7) = (-1)*(-7) = 1 * 7 = 7

Our equation now is,

(-7)^2 + 7 - 6

Using the same argument as above for two negative numbers multiplied together,

(-7)^2 = (-7)*(-7) = 7 * 7 = 49.

Our equation now is,

49 + 7 - 6

49 + 1

**50**